A PPS reinforced material with high thermal conductivity and preparation method thereof
By mixing components such as thermal conductivity agents with polyphenylene sulfide and using mechanical stirring, ball milling and hot pressing molding, a highly thermally conductive PPS reinforcement material was prepared, which solved the problem that a single PPS material could not meet the heat dissipation needs, and achieved the High thermal conductivity, heat resistance and thermal stability of the material.
Patent Information
- Application Number
- CN202410714227.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-04
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-06-04
AI Technical Summary
A single PPS material cannot meet the heat dissipation needs in real applications, which affects its service life.
Components such as polyphenylene sulfide, thermal conducting agent, thermal stabilizer, flame retardant, inhibitor, anti-drip agent, morphological proppant and colorant are mixed in a specific proportion and are subject to mechanical stirring, ball milling and hot pressing High thermal conductivity PPS reinforcement materials are prepared by molding and other processes.
It realizes high thermal conductivity, heat resistance and thermal stability of PPS materials, improves the reliability and service life of the materials, and expands the application fields of materials.
Smart Images

Figure CN118515974B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and more specifically discloses a PPS reinforced material with high thermal conductivity and a preparation method thereof. Background Art
[0002] Polyphenylene sulfide (PPS) is a relatively common polymer and a new type of high-performance thermoplastic resin with phenylthio groups. With the development of society, a single PPS material can no longer meet the application of materials in reality, especially the ability to dissipate heat in a timely manner has become an important limiting factor affecting its service life. In order to ensure the reliability of the material, it is urgent to develop a thermally conductive polymer composite material with high reliability and high heat dissipation to replace traditional polymer materials. This is the goal that all companies are constantly pursuing and researching. Summary of the invention
[0003] The present invention mainly provides a PPS reinforced material with high thermal conductivity and a preparation method thereof, which can solve the problem that a single PPS material cannot meet the application requirements in reality.
[0004] To solve the above technical problems, according to one aspect of the present invention, a PPS reinforced material with high thermal conductivity is provided, comprising the following components in parts by weight: 60-70 parts of polyphenylene sulfide, 10-20 parts of thermal conductor, 2-5 parts of heat stabilizer, 2-6 parts of inhibitor, 0.5-4 parts of flame retardant, 0.5-1.5 parts of anti-dripping agent, 1-2.5 parts of morphological support agent, 2-4 parts of filler dispersant, 1-3 parts of colorant, and 2-8 parts of compatibilizer.
[0005] Furthermore, the thermal conductor is a chimeric composition of high thermal conductivity carbon powder and copper complex; wherein the copper complex accounts for 30%-40% of the mass fraction of the composition, and the flaky high thermal conductivity carbon powder accounts for 60%-70% of the mass fraction of the composition; the copper complex is any one of copper-PAN complex, copper citrate, ammonium copper citrate and disodium copper ethylenediaminetetraacetate; the flaky high thermal conductivity carbon powder has a radial width of 20-100 μm;
[0006] The heat stabilizer is any one of 2-hydroxy-1,2,3-propanetricarboxylic acid barium salt, diazine dicarboxylic acid barium salt, tribasic lead sulfate, dibasic lead phosphite, rare earth stearate, and rare earth salicylate;
[0007] The inhibitor is any one or more of zinc oxide, aluminum hydroxide, ammonium phosphate, polyethylene terephthalate, and polybutylene terephthalate;
[0008] The flame retardant is one or more of antimony trioxide, brominated polystyrene, sodium hexametaphosphate, and potassium aluminum silicate; the particle size of the flame retardant is 30-70 μm;
[0009] The anti-dripping agent is one or more of anti-dripping agent K-PT200, anti-dripping agent MP-40, tetrafluoroethylene-ethylene copolymer, polyvinylidene fluoride, tetrafluoroethylene hexafluoropropylene, and tetrafluoroethylene alkylethylene;
[0010] The morphological proppant is any one of a bird's nest proppant and a multi-toothed ring alumina ceramic column; the particle size of the morphological proppant is 3-6 mm;
[0011] The filler dispersant is one or more of sodium stearate, sodium citrate, hexadecyltrimethylammonium bromide, dodecyl dihydroxyethyl calcium oxide, and aluminum oxide;
[0012] The colorant is one or more of titanium nickel yellow, titanium chrome brown, cobalt blue, cobalt green, copper chrome black, bismuth yellow, and iron zinc chrome brown;
[0013] The compatibilizer is any one of polypropylene grafted polystyrene and maleic anhydride grafted polypropylene.
[0014] According to another aspect of the present invention, there is provided a method for preparing a PPS reinforced material with high thermal conductivity, comprising the following steps:
[0015] S1. Dissolve the copper complex in methanol, add flaky high thermal conductivity carbon powder, mechanically stir and mix, filter and dry to obtain powder 1;
[0016] S2, mixing polyphenylene sulfide, a heat stabilizer, a flame retardant, an inhibitor, an anti-dripping agent, a filler dispersant, and a colorant, and ball-milling to obtain a powder material 2;
[0017] S3, mixing the powder 1 obtained in step S1 with the powder 2 and sieving them to obtain powder 3;
[0018] S4, heating and melting the powder obtained in step S3, adding a morphological proppant, mixing evenly, pressing into a mold, cooling and demoulding.
[0019] Furthermore, in step S1, the thermal conductor is interlocked and blended; the interlocking and blending step is: add the copper complex into a round-bottom flask, add methanol and stir to dissolve, add flaky high thermal conductivity carbon powder and stir to mix for 20 minutes, filter and dry to obtain a uniformly interlocked thermal conductor.
[0020] When the thermal conductor is mixed in the mixing step, the weight ratio of the copper complex to the flaky high thermal conductivity carbon powder is 0.42-0.67.
[0021] In step S1, step S2, and step S4, the weight proportions of polyphenylene sulfide, thermal conductor, thermal stabilizer, flame retardant, inhibitor, anti-dripping agent, morphological support agent, filler dispersant, colorant, and compatibilizer are 60-70 parts, 10-20 parts, 2-5 parts, 0.5-4 parts, 2-6 parts, 0.5-1.5 parts, 1-2.5 parts, 2-4 parts, 1-3 parts, and 2-8 parts, respectively.
[0022] The thermal conductive agent in step S1 is a copper complex and a flaky high thermal conductivity carbon powder intercalation. The intercalation method is to dissolve the copper complex in methanol, add the flaky high thermal conductivity carbon powder, and mechanically stir, blend and intercalate. The stirring, blending and intercalation time is 20 minutes.
[0023] The heat stabilizer in step S2 is any one of 2-hydroxy-1,2,3-propanetricarboxylic acid barium salt, diazine dicarboxylic acid barium salt, tribasic lead sulfate, dibasic lead phosphite, rare earth stearate, and rare earth salicylate. The flame retardant is one or more of antimony trioxide, brominated polystyrene, sodium hexametaphosphate, and potassium aluminum silicate; the particle size of the flame retardant is 30-70 μm. The inhibitor is any one or more of zinc oxide, aluminum hydroxide, ammonium phosphate, polyethylene terephthalate, and polybutylene terephthalate. The anti-drip agent is one or more of anti-drip agent K-PT200, anti-drip agent MP-40, tetrafluoroethylene-ethylene copolymer, polyvinylidene fluoride, tetrafluoroethylene hexafluoropropylene, and tetrafluoroethylene alkylethylene. The colorant is one or more of titanium nickel yellow, titanium chrome brown, cobalt blue, cobalt green, copper chrome black, bismuth yellow, and iron zinc chrome brown. The compatibilizer is any one of polypropylene grafted polystyrene and maleic anhydride grafted polypropylene. The grinding method is ball milling, and the ball milling time is 1 hour.
[0024] The sieving in step S3 is through a 200-mesh sieve.
[0025] The morphological proppant in step S4 is any one of a bird's nest proppant and a multi-toothed ring alumina ceramic column; the particle size of the morphological proppant is 3-6mm. The melting temperature is 450℃; the heating and melting adopts a heating method combining direct linear heating and gradient heating. When it is lower than 300℃, direct linear heating is adopted, and the heating rate is 5.0-9.0℃ / min; when it is higher than 300℃, gradient heating is adopted, 300℃-400℃, the heating rate is 2.0-3.5℃ / min, and the temperature is stable for 10min when it rises to 400℃; 400℃-450℃, the heating rate is 1.0-1.5℃ / min; after the temperature rises to 450℃, the temperature is kept warm and stirred for 0.5-1h; the pressure of pressing into the mold after melting is 20-30MPa, and the pressure is maintained for 10-20min after pressing into the mold; then the temperature is naturally cooled to room temperature, and after it drops to room temperature, it is left to stand for 1-1.5h.
[0026] In order to achieve the characteristics of high thermal conductivity, heat resistance and thermal stability of PPS materials, the present invention provides a method of modifying PPS by filling. Because this material has high thermal conductivity, the heat generated by the equipment can be dissipated in time without heat accumulation; and because it has heat resistance and thermal stability, accidents caused by high temperature can be avoided. By filling some colorants, PPS can be made colorful, which broadens the application field of PPS materials.
[0027] The beneficial effects of the PPS reinforced material with high thermal conductivity and the preparation method thereof of the present invention are:
[0028] (1) The present invention adds a thermal conductor, a heat stabilizer, a flame retardant, an inhibitor, an anti-dripping agent, a morphological support agent and a colorant to PPS at the same time, so that the composite material has high thermal conductivity, heat resistance and thermal stability at the same time.
[0029] (2) The present invention adds a filler dispersant and a compatibilizer to the mixed raw materials, thereby increasing the compatibility between the surface of the filler and the interface of PPS and the uniformity of filler dispersion, making it more uniform while achieving molecular-level fusion, thereby avoiding the problem of local defects in the synthesized composite material.
[0030] (3) The composite material synthesized by the present invention has a simple preparation process and is suitable for industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The present invention is further described in detail below with reference to the accompanying drawings and specific implementation methods.
[0032] Figure 1 This is a data diagram of the implementation of the thermogravimetric analyzer in Example 1;
[0033] Figure 2 This is a data diagram of the thermogravimetric analyzer implementation of Example 2;
[0034] Figure 3 This is a data diagram of the implementation of the thermogravimetric analyzer in Example 3;
[0035] Figure 4 This is a data diagram of the thermogravimetric analyzer implementation of Example 4;
[0036] Figure 5 This is a data diagram of the thermogravimetric analyzer implementation of Example 5;
[0037] Figure 6 This is a data diagram of the thermogravimetric analyzer implementation of Example 6;
[0038] Figure 7 This is a data diagram of the thermogravimetric analyzer implementation of Example 7;
[0039] Figure 8This is a data diagram of the thermogravimetric analyzer for comparative example 1;
[0040] Fig. 9 Thermogravimetric analyzer implementation data diagram for comparative example 2;
[0041] Fig.10 Thermogravimetric analyzer implementation data diagram for comparative example three;
[0042] Fig.11 This is a data diagram of the thermogravimetric analyzer for comparative example 4;
[0043] Fig.12 Thermogravimetric analysis data graph for comparative example 5;
[0044] Fig.13 This is a data diagram of the thermogravimetric analyzer implementation of comparative example 6;
[0045] Fig.14 Thermogravimetric analyzer data diagram for comparative example 7;
[0046] Fig.15 This is a graph showing the data from the thermogravimetric analyzer for comparative example eight. DETAILED DESCRIPTION
[0047] The present invention will be described in detail below with reference to the accompanying drawings and in combination with embodiments. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other without conflict.
[0048] In the following examples and comparative examples, the thermal conductivity of the composite material was tested by a flash thermal conductivity instrument. The thermal conductivity measurement range of the instrument is: 0.1-2000 W / mK, the measurement time is 1-10 ms, the accuracy is better than 3%, and the temperature range is: room temperature-500°C. The thermal stability of the composite material was evaluated by a thermal gravimetric analyzer experimental method. The temperature measurement range of the instrument is: 50-1000°C, and the accuracy is ±0.01 mg. The heat resistance of the composite material was tested by a Martin heat resistance instrument.
[0049] Embodiment 1
[0050] (1) First, 9 g of copper-PAN complex was added to a round-bottom flask, 40 g of methanol was added, heated to 40° C., and stirred to dissolve, 21 g of flaky high thermal conductivity carbon powder was added, stirring was started, and the mixture was mixed for 20 min, filtered, and dried at 50° C. for later use;
[0051] (2) 120 g of polyphenylene sulfide powder, 6 g of barium diazine dicarboxylate, 4 g of antimony trioxide, 6 g of polybutylene terephthalate, 1 g of tetrafluoroethylene hexafluoropropylene, 6 g of hexadecyltrimethylammonium bromide, 4 g of titanium nickel yellow, and 10 g of polypropylene grafted polystyrene were physically mixed, and then the mixture was placed in a ball mill for 30 min. The obtained powder was transferred to a round-bottom flask, the thermal conductor of step (1) was added, and mechanical stirring and mixing were performed for 30 min;
[0052] (3) passing the mixture obtained in step (2) through a 200-mesh sieve;
[0053] (4) The sieved mixed material is heated to melt under argon protection. When the temperature is below 300°C, the heating rate is 6.0°C / min; when the temperature is between 300°C and 400°C, the heating rate is 3.0°C / min. When the temperature reaches 400°C, the temperature is kept stable for 10 minutes; when the temperature is between 400°C and 450°C, the heating rate is 1.0°C / min. After the temperature reaches 450°C, 2 g of multi-toothed alumina ceramic columns are added, and the mixture is kept warm and stirred for 0.5-1 hour for melting.
[0054] (5) The molten mixture is hot-pressed at 20 MPa and the pressure is maintained for 20 minutes. The hot-pressed pre-finished product is then cooled to room temperature and taken out. The pre-finished product is sealed and allowed to stand at normal pressure for 1 hour to obtain a composite PPS material sheet.
[0055] Embodiment 2
[0056] (1) First, 9 g of copper-PAN complex was added to a round-bottom flask, 40 g of methanol was added, heated to 40° C., and stirred to dissolve, 21 g of flaky high thermal conductivity carbon powder was added, stirring was started, and the mixture was mixed for 20 min, filtered, and dried at 50° C. for later use;
[0057] (2) 130 g of polyphenylene sulfide powder, 6 g of barium diazine dicarboxylate, 4 g of antimony trioxide, 6 g of polybutylene terephthalate, 1 g of tetrafluoroethylene hexafluoropropylene, 6 g of hexadecyltrimethylammonium bromide, 4 g of titanium nickel yellow, and 10 g of polypropylene grafted polystyrene were physically mixed, and then the mixture was placed in a ball mill for 30 min. The obtained powder was transferred to a round-bottom flask, the thermal conductor of step (1) was added, and mechanical stirring and mixing were performed for 30 min.
[0058] (3) passing the mixture obtained in step (2) through a 200-mesh sieve;
[0059] (4) The sieved mixed material is heated to melt under argon protection. When the temperature is below 300°C, the heating rate is 6.0°C / min; when the temperature is between 300°C and 400°C, the heating rate is 3.0°C / min. When the temperature reaches 400°C, the temperature is kept stable for 10 minutes; when the temperature is between 400°C and 450°C, the heating rate is 1.0°C / min. After the temperature reaches 450°C, 2 g of multi-toothed alumina ceramic columns are added, and the mixture is kept warm and stirred for 0.5-1 hour for melting.
[0060] (5) The molten mixture is hot-pressed at 20 MPa and the pressure is maintained for 20 minutes. The hot-pressed pre-finished product is then cooled to room temperature and taken out. The pre-finished product is sealed and allowed to stand at normal pressure for 1 hour to obtain a composite PPS material sheet.
[0061] Embodiment 3
[0062] (1) First, 9 g of copper-PAN complex was added to a round-bottom flask, 40 g of methanol was added, heated to 40° C., and stirred to dissolve, 21 g of flaky high thermal conductivity carbon powder was added, stirring was started, and the mixture was mixed for 20 min, filtered, and dried at 50° C. for later use;
[0063] (2) 140 g of polyphenylene sulfide powder, 6 g of barium diazine dicarboxylate, 4 g of antimony trioxide, 6 g of polybutylene terephthalate, 1 g of tetrafluoroethylene hexafluoropropylene, 6 g of hexadecyltrimethylammonium bromide, 4 g of titanium nickel yellow, and 10 g of polypropylene grafted polystyrene were physically mixed, and then the mixture was placed in a ball mill for 30 min. The obtained powder was transferred to a round-bottom flask, the thermal conductor of step (1) was added, and mechanical stirring and mixing were performed for 30 min;
[0064] (3) passing the mixture obtained in step (2) through a 200-mesh sieve;
[0065] (4) The sieved mixed material is heated to melt under argon protection. When the temperature is below 300°C, the heating rate is 6.0°C / min; when the temperature is between 300°C and 400°C, the heating rate is 3.0°C / min. When the temperature reaches 400°C, the temperature is kept stable for 10 minutes; when the temperature is between 400°C and 450°C, the heating rate is 1.0°C / min. After the temperature reaches 450°C, 2 g of multi-toothed alumina ceramic columns are added, and the mixture is kept warm and stirred for 0.5-1 hour for melting.
[0066] (5) The molten mixture is hot-pressed at 20 MPa and the pressure is maintained for 20 minutes. The hot-pressed pre-finished product is then cooled to room temperature and taken out. The pre-finished product is sealed and allowed to stand at normal pressure for 1 hour to obtain a composite PPS material sheet.
[0067] Embodiment 4
[0068] (1) First, 6 g of copper-PAN complex was added to a round-bottom flask, 40 g of methanol was added, heated to 40° C., stirred and dissolved, 14 g of flaky high thermal conductivity carbon powder was added, stirring was started, mixed and embedded for 20 minutes, filtered, and dried at 50° C. for later use;
[0069] (2) 120 g of polyphenylene sulfide powder, 6 g of barium diazine dicarboxylate, 4 g of antimony trioxide, 6 g of polybutylene terephthalate, 1 g of tetrafluoroethylene hexafluoropropylene, 6 g of hexadecyltrimethylammonium bromide, 4 g of titanium nickel yellow, and 10 g of polypropylene grafted polystyrene were physically mixed, and then the mixture was placed in a ball mill for 30 min. The obtained powder was transferred to a round-bottom flask, the thermal conductor of step (1) was added, and mechanical stirring and mixing were performed for 30 min;
[0070] (3) passing the mixture obtained in step (2) through a 200-mesh sieve;
[0071] (4) The sieved mixed material is heated to melt under argon protection. When the temperature is below 300°C, the heating rate is 6.0°C / min; when the temperature is between 300°C and 400°C, the heating rate is 3.0°C / min. When the temperature reaches 400°C, the temperature is kept stable for 10 minutes; when the temperature is between 400°C and 450°C, the heating rate is 1.0°C / min. After the temperature reaches 450°C, 2 g of multi-toothed alumina ceramic columns are added, and the mixture is kept warm and stirred for 0.5-1 hour for melting.
[0072] (5) The molten mixture is hot-pressed at 20 MPa and the pressure is maintained for 20 minutes. The hot-pressed pre-finished product is then cooled to room temperature and taken out. The pre-finished product is sealed and allowed to stand at normal pressure for 1 hour to obtain a composite PPS material sheet.
[0073] Embodiment 5
[0074] (1) First, 9 g of copper-PAN complex was added to a round-bottom flask, 40 g of methanol was added, heated to 40° C., and stirred to dissolve, 21 g of flaky high thermal conductivity carbon powder was added, stirring was started, and the mixture was mixed for 20 min, filtered, and dried at 50° C. for later use;
[0075] (2) 120 g of polyphenylene sulfide powder, 4 g of barium diazine dicarboxylate, 4 g of antimony trioxide, 6 g of polybutylene terephthalate, 1 g of tetrafluoroethylene hexafluoropropylene, 6 g of hexadecyltrimethylammonium bromide, 4 g of titanium nickel yellow, and 10 g of polypropylene grafted polystyrene were physically mixed, and then the mixture was placed in a ball mill for 30 min. The obtained powder was transferred to a round-bottom flask, the thermal conductor of step (1) was added, and mechanical stirring and mixing were performed for 30 min.
[0076] (3) passing the mixture obtained in step (2) through a 200-mesh sieve;
[0077] (4) The sieved mixed material is heated to melt under argon protection. When the temperature is below 300°C, the heating rate is 6.0°C / min; when the temperature is between 300°C and 400°C, the heating rate is 3.0°C / min. When the temperature reaches 400°C, the temperature is kept stable for 10 minutes; when the temperature is between 400°C and 450°C, the heating rate is 1.0°C / min. After the temperature reaches 450°C, 2 g of multi-toothed alumina ceramic columns are added, and the mixture is kept warm and stirred for 0.5-1 hour for melting.
[0078] (5) The molten mixture is hot-pressed at 20 MPa and the pressure is maintained for 20 minutes. The hot-pressed pre-finished product is then cooled to room temperature and taken out. The pre-finished product is sealed and allowed to stand at normal pressure for 1 hour to obtain a composite PPS material sheet.
[0079] Embodiment 6
[0080] (1) First, 9 g of copper-PAN complex was added to a round-bottom flask, 40 g of methanol was added, heated to 40° C., and stirred to dissolve, 21 g of flaky high thermal conductivity carbon powder was added, stirring was started, and the mixture was mixed for 20 min, filtered, and dried at 50° C. for later use;
[0081] (2) 120 g of polyphenylene sulfide powder, 6 g of barium diazine dicarboxylate, 4 g of antimony trioxide, 12 g of polybutylene terephthalate, 1 g of tetrafluoroethylene hexafluoropropylene, 6 g of hexadecyltrimethylammonium bromide, 4 g of titanium nickel yellow, and 10 g of polypropylene grafted polystyrene were physically mixed, and then the mixture was placed in a ball mill for 30 min. The obtained powder was transferred to a round-bottom flask, the thermal conductor of step (1) was added, and mechanical stirring and mixing were performed for 30 min.
[0082] (3) passing the mixture obtained in step (2) through a 200-mesh sieve;
[0083] (4) The sieved mixed material is heated to melt under argon protection. When the temperature is below 300°C, the heating rate is 6.0°C / min; when the temperature is between 300°C and 400°C, the heating rate is 3.0°C / min. When the temperature reaches 400°C, the temperature is kept stable for 10 minutes; when the temperature is between 400°C and 450°C, the heating rate is 1.0°C / min. After the temperature reaches 450°C, 2 g of multi-toothed alumina ceramic columns are added, and the mixture is kept warm and stirred for 0.5-1 hour for melting.
[0084] (5) The molten mixture is hot-pressed at 20 MPa and the pressure is maintained for 20 minutes. The hot-pressed pre-finished product is then cooled to room temperature and taken out. The pre-finished product is sealed and allowed to stand at normal pressure for 1 hour to obtain a composite PPS material sheet.
[0085] Embodiment 7
[0086] (1) First, 9 g of copper-PAN complex was added to a round-bottom flask, 40 g of methanol was added, heated to 40° C., and stirred to dissolve, 21 g of flaky high thermal conductivity carbon powder was added, stirring was started, and the mixture was mixed for 20 min, filtered, and dried at 50° C. for later use;
[0087] (2) 120 g of polyphenylene sulfide powder and 6 g of barium diazine dicarboxylate, 1 g of antimony trioxide, 6 g of polybutylene terephthalate, 1 g of tetrafluoroethylene hexafluoropropylene, 4 g of hexadecyltrimethylammonium bromide, 4 g of titanium nickel yellow, and 10 g of polypropylene grafted polystyrene were physically mixed, and then the mixture was placed in a ball mill for 30 min. The obtained powder was transferred to a round-bottom flask, the thermal conductor of step (1) was added, and mechanical stirring and mixing were performed for 30 min.
[0088] (3) passing the mixture obtained in step (2) through a 200-mesh sieve;
[0089] (4) The sieved mixed material is heated to melt under argon protection. When the temperature is below 300°C, the heating rate is 6.0°C / min; when the temperature is between 300°C and 400°C, the heating rate is 3.0°C / min. When the temperature reaches 400°C, the temperature is kept stable for 10 minutes; when the temperature is between 400°C and 450°C, the heating rate is 1.0°C / min. After the temperature reaches 450°C, 3 g of multi-toothed alumina ceramic columns are added, and the mixture is stirred and melted for 0.5-1 hour at the temperature maintained;
[0090] (5) The molten mixture is hot-pressed at 20 MPa and the pressure is maintained for 20 minutes. The hot-pressed pre-finished product is then cooled to room temperature and taken out. The pre-finished product is sealed and allowed to stand at normal pressure for 1 hour to obtain a composite PPS material sheet.
[0091] Comparative Example 1
[0092] (1) 120 g of PPS powder was heated and melted under argon protection. When the temperature was below 300 °C, the heating rate was 6.0 °C / min; when the temperature was between 300 °C and 400 °C, the heating rate was 3.0 °C / min. When the temperature reached 400 °C, the temperature was kept stable for 10 min; when the temperature was between 400 °C and 450 °C, the heating rate was 1.0 °C / min. After the temperature reached 450 °C, the temperature was kept stirred and melted for 0.5-1 h.
[0093] (2) The molten mixture is hot-pressed at 20 MPa and the pressure is maintained for 20 minutes. The hot-pressed pre-finished product is then cooled to room temperature and taken out. The pre-finished product is sealed and allowed to stand at normal pressure for 1 hour to obtain a composite PPS material sheet.
[0094] Comparative Example 2
[0095] (1) 120 g of polyphenylene sulfide powder, 6 g of barium diazine dicarboxylate, 4 g of antimony trioxide, 6 g of polybutylene terephthalate, 1 g of tetrafluoroethylene hexafluoropropylene, 6 g of hexadecyltrimethylammonium bromide, 4 g of titanium nickel yellow, and 10 g of polypropylene grafted polystyrene were physically mixed, and then the mixture was placed in a ball mill and milled for 30 min;
[0096] (2) passing the mixture obtained in step (1) through a 200-mesh sieve;
[0097] (3) The sieved mixed material is heated to melt under argon protection. When the temperature is below 300°C, the heating rate is 6.0°C / min; when the temperature is between 300°C and 400°C, the heating rate is 3.0°C / min. When the temperature reaches 400°C, the temperature is kept stable for 10 minutes; when the temperature is between 400°C and 450°C, the heating rate is 1.0°C / min. After the temperature reaches 450°C, 2g of multi-toothed alumina ceramic columns are added, and the mixture is kept warm and stirred for 0.5-1h to melt.
[0098] (4) The molten mixture is hot-pressed at 20 MPa and the pressure is maintained for 20 minutes. The hot-pressed pre-finished product is then cooled to room temperature and taken out. The pre-finished product is sealed and allowed to stand at normal pressure for 1 hour to obtain a composite PPS material sheet.
[0099] Comparative Example 3
[0100] (1) First, 9 g of copper-PAN complex was added to a round-bottom flask, 40 g of methanol was added, heated to 40° C., and stirred to dissolve, 21 g of flaky high thermal conductivity carbon powder was added, stirring was started, and the mixture was mixed for 20 min, filtered, and dried at 50° C. for later use;
[0101] (2) 120 g of polyphenylene sulfide powder, 4 g of antimony trioxide, 6 g of polybutylene terephthalate, 1 g of tetrafluoroethylene hexafluoropropylene, 6 g of hexadecyltrimethylammonium bromide, 4 g of titanium nickel yellow, and 10 g of polypropylene grafted polystyrene were physically mixed, and then the mixture was placed in a ball mill for 30 min. The obtained powder was transferred to a round-bottom flask, the thermal conductor of step (1) was added, and mechanical stirring and mixing were performed for 30 min;
[0102] (3) passing the mixture obtained in step (2) through a 200-mesh sieve;
[0103] (4) The sieved mixed material is heated to melt under argon protection. When the temperature is below 300°C, the heating rate is 6.0°C / min; when the temperature is between 300°C and 400°C, the heating rate is 3.0°C / min. When the temperature reaches 400°C, the temperature is kept stable for 10 minutes; when the temperature is between 400°C and 450°C, the heating rate is 1.0°C / min. After the temperature reaches 450°C, 2 g of multi-toothed alumina ceramic columns are added, and the mixture is kept warm and stirred for 0.5-1 hour for melting.
[0104] (5) The molten mixture is hot-pressed at 20 MPa and the pressure is maintained for 20 minutes. The hot-pressed pre-finished product is then cooled to room temperature and taken out. The pre-finished product is sealed and allowed to stand at normal pressure for 1 hour to obtain a composite PPS material sheet.
[0105] Comparative Example 4
[0106] (1) First, 9 g of copper-PAN complex was added to a round-bottom flask, 40 g of methanol was added, heated to 40° C., and stirred to dissolve, 21 g of flaky high thermal conductivity carbon powder was added, stirring was started, and the mixture was mixed for 20 min, filtered, and dried at 50° C. for later use;
[0107] (2) 120 g of polyphenylene sulfide powder, 6 g of barium diazine dicarboxylate, 6 g of polybutylene terephthalate, 1 g of tetrafluoroethylene hexafluoropropylene, 6 g of hexadecyltrimethylammonium bromide, 4 g of titanium nickel yellow, and 10 g of polypropylene grafted polystyrene were physically mixed, and then the mixture was placed in a ball mill for 30 min. The obtained powder was transferred to a round-bottom flask, the thermal conductor of step (1) was added, and mechanical stirring and mixing were performed for 30 min;
[0108] (3) passing the mixture obtained in step (2) through a 200-mesh sieve;
[0109] (4) The sieved mixed material is heated to melt under argon protection. When the temperature is below 300°C, the heating rate is 6.0°C / min; when the temperature is between 300°C and 400°C, the heating rate is 3.0°C / min. When the temperature reaches 400°C, the temperature is kept stable for 10 minutes; when the temperature is between 400°C and 450°C, the heating rate is 1.0°C / min. After the temperature reaches 450°C, 2 g of multi-toothed alumina ceramic columns are added, and the mixture is kept warm and stirred for 0.5-1 hour for melting.
[0110] (5) The molten mixture is hot-pressed at 20 MPa and the pressure is maintained for 20 minutes. The hot-pressed pre-finished product is then cooled to room temperature and taken out. The pre-finished product is sealed and allowed to stand at normal pressure for 1 hour to obtain a composite PPS material sheet.
[0111] Comparative Example 5
[0112] (1) First, 9 g of copper-PAN complex was added to a round-bottom flask, 40 g of methanol was added, heated to 40° C., and stirred to dissolve, 21 g of flaky high thermal conductivity carbon powder was added, stirring was started, and the mixture was mixed for 20 min, filtered, and dried at 50° C. for later use;
[0113] (2) 120 g of polyphenylene sulfide powder, 6 g of barium diazine dicarboxylate, 4 g of antimony trioxide, 1 g of tetrafluoroethylene hexafluoropropylene, 6 g of hexadecyltrimethylammonium bromide, 4 g of titanium nickel yellow, and 10 g of polypropylene grafted polystyrene were physically mixed, and then the mixture was placed in a ball mill for 30 min. The obtained powder was transferred to a round-bottom flask, the thermal conductor of step (1) was added, and mechanical stirring and mixing were performed for 30 min.
[0114] (3) passing the mixture obtained in step (2) through a 200-mesh sieve;
[0115] (4) The sieved mixed material is heated to melt under argon protection. When the temperature is below 300°C, the heating rate is 6.0°C / min; when the temperature is between 300°C and 400°C, the heating rate is 3.0°C / min. When the temperature reaches 400°C, the temperature is kept stable for 10 minutes; when the temperature is between 400°C and 450°C, the heating rate is 1.0°C / min. After the temperature reaches 450°C, 2 g of multi-toothed alumina ceramic columns are added, and the mixture is kept warm and stirred for 0.5-1 hour for melting.
[0116] (5) The molten mixture is hot-pressed at 20 MPa and the pressure is maintained for 20 minutes. The hot-pressed pre-finished product is then cooled to room temperature and taken out. The pre-finished product is sealed and allowed to stand at normal pressure for 1 hour to obtain a composite PPS material sheet.
[0117] Comparative Example 6
[0118] (1) First, 9 g of copper-PAN complex was added to a round-bottom flask, 40 g of methanol was added, heated to 40° C., and stirred to dissolve, 21 g of flaky high thermal conductivity carbon powder was added, stirring was started, and the mixture was mixed for 20 min, filtered, and dried at 50° C. for later use;
[0119] (2) 120 g of polyphenylene sulfide powder, 6 g of barium diazine dicarboxylate, 4 g of antimony trioxide, 6 g of polybutylene terephthalate, 6 g of hexadecyltrimethylammonium bromide, 4 g of titanium nickel yellow, and 10 g of polypropylene grafted polystyrene were physically mixed, and then the mixture was placed in a ball mill for 30 min. The obtained powder was transferred to a round-bottom flask, the thermal conductor of step (1) was added, and mechanical stirring and mixing were performed for 30 min;
[0120] (3) passing the mixture obtained in step (2) through a 200-mesh sieve;
[0121] (4) The sieved mixed material is heated to melt under argon protection. When the temperature is below 300°C, the heating rate is 6.0°C / min; when the temperature is between 300°C and 400°C, the heating rate is 3.0°C / min. When the temperature reaches 400°C, the temperature is kept stable for 10 minutes; when the temperature is between 400°C and 450°C, the heating rate is 1.0°C / min. After the temperature reaches 450°C, 2 g of multi-toothed alumina ceramic columns are added, and the mixture is kept warm and stirred for 0.5-1 hour for melting.
[0122] (5) The molten mixture is hot-pressed at 20 MPa and the pressure is maintained for 20 minutes. The hot-pressed pre-finished product is then cooled to room temperature and taken out. The pre-finished product is sealed and allowed to stand at normal pressure for 1 hour to obtain a composite PPS material sheet.
[0123] Comparative Example 7
[0124] (1) First, 9 g of copper-PAN complex was added to a round-bottom flask, 40 g of methanol was added, heated to 40° C., and stirred to dissolve, 21 g of flaky high thermal conductivity carbon powder was added, stirring was started, and the mixture was mixed for 20 min, filtered, and dried at 50° C. for later use;
[0125] (2) 120 g of polyphenylene sulfide powder, 6 g of barium diazine dicarboxylate, 4 g of antimony trioxide, 6 g of polybutylene terephthalate, 1 g of tetrafluoroethylene hexafluoropropylene, 4 g of titanium nickel yellow, and 10 g of polypropylene grafted polystyrene were physically mixed, and then the mixture was placed in a ball mill for 30 min. The obtained powder was transferred to a round-bottom flask, the thermal conductor of step (1) was added, and mechanical stirring and mixing were performed for 30 min.
[0126] (3) passing the mixture obtained in step (2) through a 200-mesh sieve;
[0127] (4) The sieved mixed material is heated to melt under argon protection. When the temperature is below 300°C, the heating rate is 6.0°C / min; when the temperature is between 300°C and 400°C, the heating rate is 3.0°C / min. When the temperature reaches 400°C, the temperature is kept stable for 10 minutes; when the temperature is between 400°C and 450°C, the heating rate is 1.0°C / min. After the temperature reaches 450°C, 2 g of multi-toothed alumina ceramic columns are added, and the mixture is kept warm and stirred for 0.5-1 hour for melting.
[0128] (5) The molten mixture is hot-pressed at 20 MPa and the pressure is maintained for 20 minutes. The hot-pressed pre-finished product is then cooled to room temperature and taken out. The pre-finished product is sealed and allowed to stand at normal pressure for 1 hour to obtain a composite PPS material sheet.
[0129] Comparative Example 8
[0130] (1) First, 9 g of copper-PAN complex was added to a round-bottom flask, 40 g of methanol was added, heated to 40° C., and stirred to dissolve, 21 g of flaky high thermal conductivity carbon powder was added, stirring was started, and the mixture was mixed for 20 min, filtered, and dried at 50° C. for later use;
[0131] (2) 120 g of polyphenylene sulfide powder, 6 g of barium diazine dicarboxylate, 4 g of antimony trioxide, 6 g of polybutylene terephthalate, 1 g of tetrafluoroethylene hexafluoropropylene, 6 g of hexadecyltrimethylammonium bromide, and 4 g of titanium nickel yellow were physically mixed, and then the mixture was placed in a ball mill for 30 min. The obtained powder was transferred to a round-bottom flask, the thermal conductor of step (1) was added, and mechanical stirring and mixing were performed for 30 min.
[0132] (3) passing the mixture obtained in step (2) through a 200-mesh sieve;
[0133] (4) The sieved mixed material is heated to melt under argon protection. When the temperature is below 300°C, the heating rate is 6.0°C / min; when the temperature is between 300°C and 400°C, the heating rate is 3.0°C / min. When the temperature reaches 400°C, the temperature is kept stable for 10 minutes; when the temperature is between 400°C and 450°C, the heating rate is 1.0°C / min. After the temperature reaches 450°C, the mixture is kept warm and stirred for 0.5-1h.
[0134] (5) The molten mixture is hot-pressed at 20 MPa and the pressure is maintained for 20 minutes. The hot-pressed pre-finished product is then cooled to room temperature and taken out. The pre-finished product is sealed and allowed to stand at normal pressure for 1 hour to obtain a composite PPS material sheet.
[0135] The thermal conductivity, heat resistance and thermal stability of the PPS composite materials prepared in the examples and comparative examples were tested. The specific data are shown in Table 1.
[0136] Table 1 Test results of composite materials of embodiments and comparative examples
[0137]
[0138]
[0139] As shown in Table 1, by blending the thermal conductive component, the thermal stable component, the flame retardant component, the anti-drip component, the filler dispersion component, the morphology support component with PPS, the thermal conductivity and heat resistance of the PPS board can be significantly improved, thereby preparing a PPS with high thermal conductivity and excellent heat resistance.
[0140] Composite materials.
[0141] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention also fall within the protection scope of the present invention.
Claims
1. A PPS reinforced material with high thermal conductivity, characterized in that: The invention comprises the following components in parts by weight: 60-70 parts of polyphenylene sulfide, 10-20 parts of thermal conductor, 2-5 parts of thermal stabilizer, 2-6 parts of inhibitor, 0.5-4 parts of flame retardant, 0.5-1.5 parts of anti-dripping agent, 1-2.5 parts of morphological support agent, 2-4 parts of filler dispersant, 1-3 parts of colorant, and 2-8 parts of compatibilizer; The thermal conductor is a chimeric composition of high thermal conductivity carbon powder and copper complex, wherein the copper complex accounts for 30%-40% of the composition by mass, the flaky high thermal conductivity carbon powder accounts for 60%-70% of the composition by mass, the copper complex is a copper-PAN complex, and the flaky high thermal conductivity carbon powder has a radial width of 20-100 μm; The heat stabilizer is barium diazine dicarboxylate salt; The inhibitor is polybutylene terephthalate; The flame retardant is antimony trioxide, and the particle size of the flame retardant is 30-70 μm; The anti-drip agent is tetrafluoroethylene hexafluoropropylene; The morphological proppant is a multi-toothed ring alumina ceramic column, and the particle size of the morphological proppant is 3-6mm; The filler dispersant is hexadecyltrimethylammonium bromide; The colorant is titanium nickel yellow; The compatibilizer is polypropylene grafted polystyrene.
2. The method for preparing a PPS reinforced material with high thermal conductivity according to claim 1, characterized in that: The following steps are involved: S1. Dissolve the copper complex in methanol, add flaky high thermal conductivity carbon powder, mechanically stir and mix, filter and dry to obtain powder 1; S2, mixing polyphenylene sulfide, a heat stabilizer, a flame retardant, an inhibitor, an anti-dripping agent, a filler dispersant, and a colorant, and ball-milling to obtain a powder material 2; S3, mixing the powder 1 obtained in step S1 with the powder 2 and sieving them to obtain powder 3; S4, heating and melting the powder obtained in step S3, adding a morphological proppant, mixing evenly, pressing into a mold, cooling and demoulding.
3. The method for preparing a PPS reinforced material with high thermal conductivity according to claim 2, characterized in that: The preparation steps of the powder material 1 in step S1 are as follows: adding the copper complex into a round-bottom flask, adding methanol and stirring to dissolve, adding flaky high thermal conductivity carbon powder and stirring to mix for 20 minutes, and filtering and drying.
4. The PPS reinforced material with high thermal conductivity and the preparation method thereof according to claim 2, characterized in that: The heating and melting temperature in step S4 is 450°C.
5. The method for preparing a PPS reinforced material with high thermal conductivity according to claim 2 or 4, characterized in that: The heating and melting in the step S4 adopts a heating method combining direct linear heating and gradient heating. When the temperature is lower than 300°C, direct linear heating is adopted with a heating rate of 5.0-9.0°C / min; when the temperature is higher than 300°C, gradient heating is adopted, 300°C-400°C, the heating rate is 2.0-3.5°C / min, and the temperature is stabilized for 10 minutes when it reaches 400°C; 400°C-450°C, the heating rate is 1.0-1.5°C / min; after the temperature reaches 450°C, the temperature is kept warm and stirred for 0.5-1h; the pressure of pressing into the mold after melting is 20-30MPa, and the pressure is maintained for 10-20min after pressing into the mold; then the temperature is naturally cooled to room temperature, and after cooling to room temperature, it is left to stand for 1-1.5h.
6. Application of the PPS reinforced material with high thermal conductivity according to claim 1 or the PPS reinforced material with high thermal conductivity prepared by the method for preparing the PPS reinforced material with high thermal conductivity according to any one of claims 2 to 5 in the fields of electronics and electrical, aerospace, communications and automobiles.
Citation Information
Patent Citations
High-CTI (comparative tracking index) value and high-thermal conductivity PPS (polyphenylene sulfide) material and preparation method thereof
CN117070063A